Orally administered conjugated linoleic acid ameliorates allergic dermatitis induced by repeated applications of oxazolone in mice. (15th March 2016) - Nakanishi, Tomonori; Tokunaga, Yuzo; Yamasaki, Masao; Erickson, Laurie; Kawahara, Satoshi
Abstract: Conjugated linoleic acid (CLA) is one of the constituents of animal products with possible health benefits such as anti‐carcinogenic and anti‐obesity effects. In this study, we investigated the immunomodulatory effects of CLA using a mouse model of allergic dermatitis. Mice were orally administered either a CLA mixture containing equal amounts of 9c, 11 t‐CLA and 10 t, 12c‐CLA, or high linoleic acid safflower oil, and allergic dermatitis was induced on the ear by repeated topical applications of oxazolone. Oral administration of the CLA mixture but not the high linoleic safflower oil attenuated the symptoms of allergic dermatitis in both ear weights and clinical scores. This effect was associated with decreased levels of ear interleukin‐4 (IL‐4) and plasma immunoglobulin E. The immunomodulatory effects of the CLA isomers were compared by an in vitro cytokine production assay. The results showed that 9c, 11 t‐CLA, the most predominant isomer in animal products, significantly inhibited IL‐4 and interferon‐γ production from mouse splenocytes with similar potency to 10 t, 12c‐CLA. These findings suggest that CLA, a constituent of animal products, has a potentially beneficial effect for amelioration of allergic dermatitis.